ANALISIS ALIRAN KAS TAHUN 2010 - 2011 PADA PT. JAYA PUTRA SEMESTA SAMARINDA - Tisna Amijaya, Andi dodi (EKONOMIA, 2014)
Cash has a very central position in an effort to support the smooth operation of the company . Adequate amount of cash is very important for the smooth running of the business to support its implementation of decisions of strategic importance . Formulation of the problem as proposed ririskiky outline the background of that cash is an important component in the company of PT . Jaya Putra Samarinda Universe . During its development , PT . Jaya Putra Samarinda Universe progressing the sale of electronic goods is increasing. Issues to be raised is whether the cash flow and liquidity PT . Jaya Putra Samarinda Universe in 2010 was higher than 2011? . whereas the purpose of this study was to compare the statements of cash flows PT . Jaya Putra Samarinda Universe if it is liquid or not by looking at the ratio of cash flow and liquidity in 2010-2011 . To see a comparison of cash flow Dapa years 2010 - 2011 and the liquidity ratio in 2010-2011 . Basic theory used in this study is financial accounting and analysis tools are used is Liquidity Ratio and Cash Flow Statement . Based on the analysis and discussion , the conclusions of this study are: 1 . Judging from the statement of cash flows PT . Jaya Putra Samarinda Universe , an increase in net cash and cash amount of cash as well . 2 . And judging by the liquidity ratio PT . Jaya Putra Samarinda Universe , Impaired . Thus, the hypothesis put forward , that the cash flow of PT . Jaya Putra Samarinda Universe higher in 2010 compared to 2011 was rejected . And hypotheses put forward for liquidity PT . Jaya Putra Samarinda Universe 2010 is higher compared to the year 2011 , be accepted.